Correlation Between Helicobacter Pylori Infection and Severity of Asthma - Abdul-Razzaq Hassan Alkaaby; Ammar Jabbar Majeed; Sadiq J. Ali Almuhana; Sabah Ali Jaber Alhelu (Kufa Journal for Nursing Sciences)
Background: Microbial exposures have been suggested to confer protection from allergic disorders, and reduced exposures to gastrointestinal microbes have been proposed as an explanation for the increase in asthma severity and prevalence. Since the general prevalence of Helicobacter pylori has been decreasing, we hypothesized that H. pylori serostatus may be inversely related to the severity of asthma.